Cucurainbow Enterprise / Jeffie Albert Amatus... [et al.] - Robert, Ester Fenny; Samit, Ivy Ernalien; Kuimin, Siti Sufina; Madran, Azeahamera; Amatus, Jeffie Albert (2014)
This business is based on partnership where it consists of five ( 5) member which hold important positions in the company such as General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM 131,920 where the total contribution when we add the amount of each member is RM 135,000 and we have a business fund from Waqaf An-Nur Corporation Berhad which is RM 12,000. To make it more attractive and interesting, we decided to make some innovation by implying our creativity and modem element in this fritters making. Nowadays, color is one of the important things in any products making so colorful fritters with flavor might be a new attraction to people. We have done some research that Malaysia is one of developed country and it quite busy during day time. Normally people who work during office hour and students do not have much time for breakfast. So, with our new innovation, they can just grab a packet of fritters with different fillings and go to work. Easy as simple as that. We will expect that our business will become more developed in the near future because with the new innovation in our fritters, the demand will increase not only during any occasion but it might be a new daily snack. This will give more advantages for us to make our product more profitable and stable in the long run.